Double hybrid DFT calculations with Slater type orbitals. Issue 18 (16th April 2020) - Förster, Arno; Visscher, Lucas
Abstract: On a comprehensive database with 1, 644 datapoints, covering several aspects of main‐group as well as of transition metal chemistry, we assess the performance of 60 density functional approximations (DFA), among them 36 double hybrids (DH). All calculations are performed using a Slater type orbital (STO) basis set of triple‐ ζ (TZ) quality and the highly efficient pair atomic resolution of the identity approach for the exchange‐ and Coulomb‐term of the KS matrix (PARI‐ K and PARI‐ J, respectively) and for the evaluation of the MP2 energy correction (PARI‐MP2). Employing the quadratic scaling SOS‐AO‐PARI‐MP2 algorithm, DHs based on the spin‐opposite‐scaled (SOS) MP2 approximation are benchmarked against a database of large molecules. We evaluate the accuracy of STO/PARI calculations for B3LYP as well as for the DH B2GP‐PLYP and show that the combined basis set and PARI‐error is comparable to the one obtained using the well‐known def2‐TZVPP Gaussian‐type basis set in conjunction with global density fitting. While quadruple‐ ζ (QZ) calculations are currently not feasible for PARI‐MP2 due to numerical issues, we show that, on the TZ level, Jacob's ladder for classifying DFAs is reproduced. However, while the best DHs are more accurate than the best hybrids, the improvements are less pronounced than the ones commonly found on the QZ level. For conformers of organic molecules and noncovalent interactions where very high accuracy is required for qualitatively correct results, DHs provide only small improvements over hybrids, while they still excel in thermochemistry, kinetics, transition metal chemistry and the description of strained organic systems. Abstract : The authors assess the accuracy of 60 density functional approximations, including 36 double hybrid functionals, using Slater type orbitals. Employing triple‐zeta quality, Basis set errors are comparable to the ones obtained from standard Gaussian type orbital basis sets. For a large data set of 1, 644 data points, Jacob's ladder is reproduced also on the triple‐zeta level. Using a modern SOS‐MP2 algorithm, very large double hybrid calculations do not require much more computational time than hybrid calculations.